Determinación de la eficiencia de remoción de contaminantes en efluentes de tratamiento de aguas residuales Covicorti mediante nanoburbujas de aire-oxígeno - Díaz Iglesias, Luz Aguedita (2019)
There are notable environmental problems related to the use and management of water, which is why industries seek clean technologies with greater efficiency in decontamination and with a minimum investment such as the application of nanobubbles in the treatment of wastewater. Therefore, the objective of this research isbased mainly on the application of air-oxygen nanobubbles in the laboratory, determining the efficiency in the removal of contaminants in the treatment of Covicorti wastewater in the City of Trujillo and to make a comparasion with the maximum permissible limits, form Peruvian Normative about water used as a recreational zone or irrigation.The experimentation of the research work was carried out with a sample of the effluent of the Aereated-facultative Lagoon from Covicorti, these waters were treated in the laboratory, in a nanobubble generating system composed of a 0.5 HP pump, air generator and medicinal oxygen connection at 0.5 psi. The effect of the air-oxygen nanobubble about the OD,DQO,DBO5, thermotolerant coliforms and heavy metal (Pb,Cd,Fe,Cu,Zn,Cr,Mn,Ba,Al,Hg) concentrations was analized. The results showed that the treatment with air-oxygen nanobubbles managed to improve the quality of the water at 20 minutes, reducing the concentration of OD in 66.68%, of COD in 64.76%, DBO5 in 66.66% and metals heavy at 28.50%